Evidence for a narrow baryonic state decaying to K(S)(0)p and K-S(0)(p)over-bar in deep inelastic scattering at HERA - Chekanov, S; Derrick, M; Loizides, J; Magill, S; Miglioranzi, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Pavel, N; Antonioli, P; Bari, G; et al. (2004)
A resonance search has been made in the K0Sp and K0Sp̄ invariant-mass spectrum measured with the ZEUS detector at HERA using an integrated luminosity of 121 pb-1. The search was performed in the central rapidity region of inclusive deep inelastic scattering at an ep centre-of-mass energy of 300-318 GeV for exchanged photon virtuality, Q2, above 1 GeV2. Recent results from fixed-target experiments give evidence for a narrow baryon resonance decaying to K+n and K0Sp, interpreted as a pentaquark. The results presented here support the existence of such state, with a mass of 1521.5±1.5(stat.)+2.8-1.7(syst.) MeV and a Gaussian width consistent with the experimental resolution of 2 MeV. The signal is visible at high Q2 and, for Q2>20 GeV2, contains 221±48 events. The probability of a similar signal anywhere in the range 1500-1560 MeV arising from fluctuations of the background is below 6×10-5. © 2004 Elsevier B.V. All rights reserved.